Johann Mattheson and the ideal of the Perfect Musician (Per Musi, 2017)
Der Vollkommene Capellmeister (“The perfect master of chapel”) is Johann Mattheson´s (1681‐1767) last and  most ambitious work. It is also the most important writing belonging to the genre of musical preceptives known as Musica Poetica, a group of treatises edited between the 16th and 18th centuries which make systematic import of concepts of the rhetoric tradition in order to describe musical elements. In this article, we concentrate on the notion of the perfect music‐orator. First, we examine the manner by which Mattheson represents himself in his autobiography, not as an individual subject, but as a type – humanist, cortesan, christian, lutheran – suggesting a reading of this work from the poetic‐rhetorical perspective. This allows us to also discuss the potential addressees of this work. This article also shows how Mattheson emulates commonplaces already presented in latin rhetoric handbooks, especially De Oratore, by Cicero, and Intitutio Oratoria, by Quintilian, when he discusses the perfect Kapellmeister. Finally, we will examine commonplaces directly connected to the idea of the Perfect Musician: the possibility to attain perfection and the requirements to accomplish it, as well as the contribution of nature and art and the importance of nonmusical knowledge to perform this task.